Madrasah dan rumah Tok Janggut, Langgar, Alor Setar, Kedah / [lukisan teknik] - Siti Aminah Abdul Manaf; Azhari Idris; Wan Yusoff Yaacub; Marsinah Slamat; Noriah Shahari; Ashaari Zainal Abidin (Kuala Lumpur : Universiti Teknologi Malaysia, 1979)
02